PROSES PERANCANGAN STRATEGI PROMOSI: Studi Kasus pada Sebuah Start-up Business - Cindy Amelia; Wirawan ED Radianto (Universitas Bunda Mulia, 2017)
The purpose of this study is to formulate promotion strategy for start-up business. In order to get comprehensive and deeper understanding this study uses qualitative approach. There are three categories of informant namely competitors, consumers, and expert. In depth interview and observation are used in collecting important data. Validity come from triangulation technique and data is analyzed by Miles and Huberman method. This study shows that there are five strategies for promotion namely social media, photography, discount, endorse, and website. Finally, attending exhibition is very important for this business in order to get many customers.Key words:promotion, strategy, start-up business, social media